Demography and dispersal ability of the Alpine Longhorn Rosalia alpina (Coleoptera: Cerambycidae) - Drag, Lukáš (Jihočeská univerzita, 2011)
This Master Thesis brings results of study on endangered species Alpine Longhorn Rosalia alpina in beech forest of National Nature Reserve Maly and Velky Bezdez and Slatinne Hills. We used mark-recapture method to study the population size, longevity and dispersal ability of this species. We also assessed the distribution pattern of the species on another 15 habitat patches in the Ralska Upland.
Demography and dispersal ability of the Alpine Longhorn Rosalia alpina (Coleoptera: Cerambycidae)
Keywords: mark-recapture; POPAN; population ecology; mobility; lifespan; Cerambycidae; beetles; mark-recapture; POPAN; population ecology; mobility; lifespan; Cerambycidae; beetles